The optimization of transducer layout in rail flaw detection - Lei Zhang; Xiao-rong Gao; Wo Wang; Chao-yong Peng (2015 IEEE Far East NDT New Technology & Application Forum (FENDT), 2015)
The railway is a kind of large volume public transportation, and more and more attention is paid to the safety of rails nowadays. As the rail is subject to heavy cyclic loads of trains, it is easily broken in the long-term operations, and this will seriously affect the safety of the trains. As an important rail flaw detection method, ultrasonic testing has been widely utilized to ensure the safety of the rail. However, the existing programs of this method normally have problems such as the deflection angle of transducer, number of transducers and frequent replacement of transducer layout. A new method was proposed in this paper, which is based on both the conventional transducer and the phased array transducer. Matlab software and acoustics approach were employed to optimize the parameters and the deflection angle of transducers. Results show that this method is experimentally reasonable and it can meet requirements of rail flaw detection.